2020
DOI: 10.1093/milmed/usz460
|View full text |Cite
|
Sign up to set email alerts
|

Implementing Evidence-Based Practice Facilitators: A Case Series

Abstract: Background In 2017, the TriService Nursing Research Program completed a strategic planning session, which identified key barriers to implementing evidence-based practice (EBP) within the U.S. Military Health System (MHS) including a focus on readiness training and deployments, frequent staff moves for military members, and relatively junior nurses in clinical roles. To facilitate EBP at individual military treatment facilities (MTFs), an EPB Facilitator role was developed using an evidence-ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 10 publications
1
7
0
Order By: Relevance
“…According to the participant's experience, despite the appropriate and accepting organizational atmosphere in the study departments and the follow-up and supervision of responsible people, including the head nurses, physicians and faculty members; The lower prioritization of managers at other levels such as clinical supervisors and their lack of information about EBP and the lack of regular monitoring have been the barrier to the implementing this process. Consistent with these findings, other studies have identified a lack of support for change (Dadich et al, 2015;Pericas-Beltran et al, 2014) and a lack of knowledge and skills in the EBP (Augustino et al, 2020;Clarke et al, 2021) as barriers to the implementing EBP. The value and priority of EBP implementation in the organization and appropriate monitoring and feedback from managers lead to the creation of a supportive organizational climate for change (Baird & Miller, 2015;Melnyk et al, 2010;Whiteside et al, 2016).…”
Section: Discussionsupporting
confidence: 68%
“…According to the participant's experience, despite the appropriate and accepting organizational atmosphere in the study departments and the follow-up and supervision of responsible people, including the head nurses, physicians and faculty members; The lower prioritization of managers at other levels such as clinical supervisors and their lack of information about EBP and the lack of regular monitoring have been the barrier to the implementing this process. Consistent with these findings, other studies have identified a lack of support for change (Dadich et al, 2015;Pericas-Beltran et al, 2014) and a lack of knowledge and skills in the EBP (Augustino et al, 2020;Clarke et al, 2021) as barriers to the implementing EBP. The value and priority of EBP implementation in the organization and appropriate monitoring and feedback from managers lead to the creation of a supportive organizational climate for change (Baird & Miller, 2015;Melnyk et al, 2010;Whiteside et al, 2016).…”
Section: Discussionsupporting
confidence: 68%
“…For example, structural characteristics such as leadership engagement, support, and commitment (Albers et al, 2021;Bach-Mortensen et al, 2018;Bauer et al, 2015;Bergmark et al, 2018;Brown et al, 2014;Ecker et al, 2021;Flodgren et al, 2012;Li et al, 2018;Ogden et al, 2016;Quinn et al, 2019;Shuman et al, 2020;Theys et al, 2020) are frequent facilitators for EBP across settings, as are initial and ongoing education and skill building for clinicians (Albers et al, 2021;Bauer et al, 2015;Bergmark et al, 2018;Bernhardsson et al, 2017;Brown et al, 2014;Eisman et al, 2020;Keurhorst et al, 2015;Li et al, 2018;McNett et al, 2021b;Shuman et al, 2020;Tucker & Gallagher-Ford, 2019;Warren et al, 2016). In addition, unit-based champions or facilitators in local clinical groups can promote routine uptake of an EBP within specific settings, as these individuals often know vital factors to support implementation (Albers et al, 2021;Augustino et al, 2020;Bergmark et al, 2018;Bernhardsson et al, 2017;Brown et al, 2014;Newhouse et al, 2013;Pellecchia et al, 2018;Theys et al, 2020;van Rooijen et al, 2021). Likewise, a team-based approach (Flodgren et al, 2012;Quinn et al, 2019;…”
Section: Facilitators To Ebp Implementationmentioning
confidence: 99%
“…Barriers to EBP implementation often reflect the absence of one or more of the factors that facilitate routine implementation in clinical settings. For example, lack of knowledge or competencies in EBP (Augustino et al, 2020;Bernhardsson et al, 2017;Clarke et al, 2021;Garcia et al, 2021;Li et al, 2018;Ogden et al, 2016;Warren et al, 2016;Yoo et al, 2019), absence of leadership support (Augustino et al, 2020;Bergmark et al, 2018;Ecker et al, 2021;Garcia et al, 2021;Li et al, 2018;Quinn et al, 2019;Shuman et al, 2020), and lack of time/resources for EBP (Bernhardsson et al, 2017;Clarke et al, 2021;Flodgren et al, 2012;Garcia et al, 2021;Li et al, 2018;McNett et al, 2021b;Quinn et al, 2019) are barriers to EBP implementation. In addition, individual factors such as resistance to change (Bauer et al, 2015;Brown et al, 2014;Clarke et al, 2021;Ecker et al, 2021;Eisman et al, 2020;Flodgren et al, 2012;Quinn et al, 2019;Theys et al, 2020;Tucker & Gallagher-Ford, 2019) and poor collaboration (Bauer et al, 2015;Bergmark et al, 2018;Bernhardsson et al, 2017;Brown et al, 2014;Clarke et al, 2021;Garcia et al, 2021;Ogden...…”
Section: Barriers To Ebp Implementationmentioning
confidence: 99%
See 2 more Smart Citations